Analisis Sektor Unggulan dengan Metode Location Quotient (LQ) di Kabupaten Pohuwato - Ramadhani, Bulan Suci; Bouty, Rahmat Firdaus (LPPM University 17 Agustus 1945 Samarinda, 2023)
This study aims to determine the leading sectors in Pohuwato Regency using LQ (Location Quetient) analysis. The research method uses descriptive quantitative analysis. Secondary data was obtained from BPS Pohuwato Regency and Gorontalo Province with the last 5 years (2018, 2019, 2020, 2021, 2022). The data is the GDP of constant prices according to business fields analyzed and processed using Microsoft Excel. The findings revealed that there are 2 base or superior sectors in Pohuwato Regency. First, the Agriculture, Forestry, and Fisheries sector. Second, namely in the processing industry sector. While the other 15 sectors include non-base (non-superior) sectors.Keywords : Base, GRDP, Location Quetient, Pohuwato, Sector